PERLINDUNGAN HUKUM MASYARAKAT ADAT DALAM SENGKETA BATAS TANAH: EVALUASI IMPLEMENTASI PP NO. 24 TAHUN 1997 DI DESA LANGGUR - Kristi Maria Hungan; Fani Clarais Hungan; Devanti Vidiasari (Jurnal Ilmiah Advokasi, 2026)
Land boundary disputes among indigenous communities frequently occur, particularly on unregistered land, leading to legal uncertainty. One such case arises in Langgur Village, Kei Kecil District, Southeast Maluku Regency, where land boundary conflicts involve the interaction between state law and customary law. This study aims to evaluate the implementation of Government Regulation No. 24 of 1997 on Land Registration in providing legal protection for indigenous communities, as well as to analyze the role of Larvul Ngabal customary law in resolving land boundary disputes in Langgur Village. The research employs an empirical socio-legal approach, with data collected through interviews, observations, and literature review. The findings reveal that legal protection for indigenous communities has not been fully effective, particularly in terms of land registration, which remains limited in practice. Legal protection mechanisms include both preventive and repressive measures; however, their implementation faces structural and cultural challenges. Meanwhile, Larvul Ngabal customary law plays a significant role in dispute resolution through mediation and consensus led by traditional authorities, which is more socially accepted within the community. This study highlights the gap between state law and customary law, emphasizing the need for an integrative approach that accommodates local values within the land registration system to ensure legal certainty and justice for indigenous communities.Keywords: Legal Protection, Indigenous Communities, Land Boundary Disputes, Customary Law, Land Registration